Control of Hypothenemus hampei (FERRARI) on yards for coffee drying / Controle da broca-do-café (Hypothenemus hampei) FERRARI em terreiros de secagem de café - Patrícia H. Santoro (Semina: Ciências Agrárias, 2003)
The coffee borer (Hypothenemus hampei), one of the main pests affecting coffee fruits under favorable conditions for development, can contribute to a reduction in productivity. The control of this insect is basically chemical, causing environmental, food and farmer contamination. Thus, alternatives must be found to reduce the use of chemical insecticides in the control of this insect. The objective of this work was to analyze, in a coffee drying area: 1) the capture efficiency of traps placed at different heights: 0, 35 and 70 cm; 2) the period of greatest collection (0 to 96 hrs) and 3) the effect of Beauveria bassiana spraying, in two concentrations, on the coffee fruits. Traps were placed around the area, and the insects were collected at 24, 48, 72,and 96 hours. At the same time, the drying fruits were sprayed with two concentrations of B. bassiana to evaluate the mortality rate caused by the fungus found in the emerged borer. Results showed no significant difference regarding the capture of the insects in the traps placed at different heights, and the 48 hour interval registered the highest number of borers collected. The highest fungus concentration (1 x 1011 canidia/ml) caused a mortality rate, attested by B. bassiana of approximately 50% of the emerged borers. A broca-do-cafeeiro (Hypothenemus hampei) é uma das principais pragas pelo ataque aos frutos que, sob condições favoráveis ao seu desenvolvimento, pode contribuir para redução da produtividade. O principal método de controle deste inseto é químico, provocando a contaminação ambiental dos alimentos e do agricultor. Assim, alternativas devem ser pesquisadas visando diminuir o uso de inseticidas químicos. O objetivo deste trabalho foi analisar, no terreiro de secagem, a eficiência de captura das armadilhas em diferentes alturas (0, 35 e 70 cm); o período de maior captura (0-96 h) e o efeito da pulverização de Beauveria bassiana, em duas concentrações, sobre os frutos de café, visando o controle da broca. As armadilhas foram distribuídas em volta do terreiro, sendo os insetos coletados às 24, 48, 72 e 96 horas. Paralelamente, foram pulverizadas, nos frutos em secagem no terreiro, duas concentrações de B. bassiana avaliando-se a mortalidade provocada pelo fungo nas brocas emergidas. Os resultados obtidos mostraram que não houve diferença significativa quanto à captura dos insetos nas diferentes alturas das armadilhas e no intervalo de 24-48 horas foi coletado o maior número de brocas. A maior concentração do fungo (1 x 1011 conídios/ml) promoveu mortalidade confirmada por B. bassiana de aproximadamente 50% das brocas emergidas.